THE IMPACT OF PERCEPTION OF GLASS CEILLING IN ORGANIZATION AND SOCIAL SUPPORT ON MOTIVATION AND ORGANIZATIONAL COMMITMENT - AYUNI, SHEILA PERMATA; HARYADI, HARYADI (JOURNAL OF RESEARCH IN MANAGEMENT, 2018)
This research takes the title: "The Influence of Individual Perception About Glass Ceilings in Organizational and Social Support Against Organizational Motivation and Commitment (Study at PT Micro Madani Institute)". The purpose of this study was to determine the effect of individual glass on the glass ceiling in the workplace and also to socialize the organization and the company. The method used is a survey with the number of respondents in this study as many as 50 respondents. The analysis used is the test of validity, reliability test, multiple regression, sobel test, and hypothesis testing. Based on the results of research and data analysis using Multiple Regression shows that: (1) Individual Perception about Glass Ceiling have an effect on to Motivation. (2) Social Support affects Motivation. (3) Motivation affects Organizational Commitment. (4) Individual Perceptions of Glass Ceiling Affects Organizational Commitment. (5) Social Support affects Organizational Commitment. (6) Motivation mediates Individual Perceptions of Glass Ceiling on Organizational Commitment. (7) Motivation mediates Social Support to Organizational Commitment. The implications of this research are the work that can be done to change the individual perceptions of glass ceiling to be better in the minds of employees by approaching female employees, providing understanding and motivation, and company policies to better accept the opinions of female employees and provide assistance to the problems faced by female employees so that female employees become more motivated to work. Co-workers who support each other and can work together, and leaders who give appreciation and appreciation will motivate employees to always give the best work of work to the company. Containers to complain of discrimination in the workplace can curb the practice of glass ceiling and enable employees to increase organizational commitment to the company. Social support from colleagues and leaders will keep employees motivated and committed and accountable to their work within the organization.